Assessing Exposures to Magnetic Resonance Imaging’s Complex Mixture of Magnetic Fields for In Vivo, In Vitro, and Epidemiologic Studies of Health Effects for Staff and Patients - Frankel, Jennifer; Wilén, Jonna; Hansson Mild, Kjell (Frontiers in Public Health, 2018)
A complex mixture of EM fields is used in MRI: static, low frequency and radio frequency magnetic fields. The static magnetic field ranges from one to several Tesla. The low-frequency field can reach several mT and with a time derivative of the order of some T/s. The RF field has a magnitude of up to several µT giving rise to SAR values of a few W/kg. Very little attention has been paid to the case where there is a combined exposure to several different fields at the same time. Some studies have shown genotoxic effects in cells after exposure to an MRI scan while others have not demonstrated any effects. A typical MRI exam includes several imaging sequences of varying length and intensity, to produce several different types of images. Each sequence is designed with a particular purpose in mind, so one sequence can, for example, be optimized for clearly showing fat-water contrast, while another is optimized for high-resolution detail. It is of the utmost importance that future experimental studies give a thorough description of the exposure they are using, and not just a statement such as “An ordinary MRI sequence was used.” Even if the sequence is specified, it can differ substantially between manufacturers on, e.g., RF pulse height, width, and duty cycle. In the latest SCENIHR opinion it is stated that there is very little information regarding the health effects of occupational exposure to MRI fields, and long-term prospective or retrospective cohort studies on workers are recommended as